Spotlight - Singer, Josh 1972-; McCarthy, Tom 1966- ([Universal Pictures], 2015)
"The true story of how the Boston Globe uncovered the massive scandal of child molestation and cover-up within the local Catholic Archdiocese, shaking the entire Catholic Church to its core."--www.imdb.com